Axenic interspecies and intraclonal hybrid formation in Leishmania: Successful crossings between visceral and cutaneous strains - Gutiérrez-Corbo, Camino; Domínguez-Asenjo, Bárbara; Pérez-Pertejo, Yolanda; García-Estrada, Carlos; Bello, Felio J; Balaña-Fouce, Rafael; Reguera, Rosa M. (PLoS neglected tropical diseases, 2022)
Diseases caused by trypanosomatids are serious public health concerns in low-income endemic countries. Leishmaniasis is presented in two main clinical forms, visceral leishmaniasis—caused by L . infantum and L . donovani —and cutaneous leishmaniasis—caused by many species, including L . major , L . tropica and L . braziliensis . As for certain other trypanosomatids, sexual reproduction has been confirmed in these parasites, and formation of hybrids can contribute to virulence, drug resistance or adaptation to the host immune system. In the present work, the capability of intraclonal and interspecies genetic exchange has been investigated using three parental strains: L . donovani , L . tropica and L . major , which have been engineered to express different fluorescent proteins and antibiotic resistance markers in order to facilitate the phenotypic selection of hybrid parasites after mating events. Stationary and exponential-phase promastigotes of each species were used, in in vitro experiments , some of them containing LULO cells (an embryonic cell line derived from Lutzomyia longipalpis ). Several intraclonal hybrids were obtained with L . tropica as crossing progenitor, but not with L . donovani or L . major . In interspecies crossings, three L . donovani x L . major hybrids and two L . donovani x L . tropica hybrids were isolated, thereby demonstrating the feasibility to obtain in vitro hybrids of parental lines causing different tropism of leishmaniasis. Ploidy analysis revealed an increase in DNA content in all hybrids compared to the parental strains, and nuclear analysis showed that interspecies hybrids are complete hybrids, i.e. each of them showing at least one chromosomal set from each parental. Regarding kDNA inheritance, discrepancies were observed between maxi and minicircle heritage. Finally, phenotypic studies showed either intermediate phenotypes in terms of growth profiles, or a decreased in vitro infection capacity compared to the parental cells. To the best of our knowledge, this is the first time that in vitro interspecies outcrossing has been demonstrated between Leishmania species with different tropism, thus contributing to shed light on the mechanisms underlying sexual reproduction in these parasites.